2011
DOI: 10.5153/sro.2341
|View full text |Cite
|
Sign up to set email alerts
|

Saints and Slackers: Challenging Discourses about the Decline of Domestic Cooking

Abstract: Amidst growing concern about both nutrition and food safety, anxiety about a loss of everyday cooking skills is a common part of public discourse. Within both the media and academia, it is widely perceived that there has been an erosion of the skills held by previous generations with the development of convenience foods and kitchen technologies cited as culpable in ‘deskilling’ current and future generations. These discourses are paralleled in policy concerns, where the incidence of indigenous food-borne disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 9 publications
2
64
0
Order By: Relevance
“…caraher, Dixon, Lang, & carr-hill, 1999), in the Uk, both popular and policy discourses alleging the decline of cooking contrast an imagined halcyon past -in which good wholesome food was cooked from 'scratch' with fresh, raw ingredients -with the culinary ignorance assumed of the present period. however, as has been illustrated elsewhere (Meah & Watson, 2011), our participants' recollections often enabled us to contest this view, some being very assertive in reporting a lack of skill or imagination on their mothers' part, or highlighting the prevalence of overcooked vegetables, which was what 'everyone did in those days really' . Moreover, in relation to our project's principal focus, one woman suggested that it was not fair to 'generalise like that … making us out to be saints with food hygiene and younger people not, and I don't think that's true' (see Meah & Watson, 2011).…”
Section: Kitchens As a Conduit To The Pastmentioning
confidence: 59%
“…caraher, Dixon, Lang, & carr-hill, 1999), in the Uk, both popular and policy discourses alleging the decline of cooking contrast an imagined halcyon past -in which good wholesome food was cooked from 'scratch' with fresh, raw ingredients -with the culinary ignorance assumed of the present period. however, as has been illustrated elsewhere (Meah & Watson, 2011), our participants' recollections often enabled us to contest this view, some being very assertive in reporting a lack of skill or imagination on their mothers' part, or highlighting the prevalence of overcooked vegetables, which was what 'everyone did in those days really' . Moreover, in relation to our project's principal focus, one woman suggested that it was not fair to 'generalise like that … making us out to be saints with food hygiene and younger people not, and I don't think that's true' (see Meah & Watson, 2011).…”
Section: Kitchens As a Conduit To The Pastmentioning
confidence: 59%
“…Furthermore, if we consider the person engaging in these household work practices over the life course, we can usefully consider the role that household work plays in personal narratives, as a way in which women conceptualise 'growing up'. As I suggested above, literature on household work has shown the relevance of mother/daughter relationships and ideas of what it means to be a 'good' mother, when making sense of women's accounts of their housework and foodwork practices (Oakley 1974;Hochschild 1989;DeVault 1991;Pilcher 1994;Bugge and Almås 2006;Curtis et al 2009;Meah and Watson 2011). However, I would argue that by thinking about household work as part of the personal life of these women, in the sense that it is a something that 'impacts closely' on them (Smart 2007: 28), and their changing sense of self, accounts of both individual responsibility and relational identities can be brought out further through a focus on how self-narratives are constructed around the theme of household work.…”
Section: Individualisation and Mothers' Relational Narrative Identitiesmentioning
confidence: 99%
“…We found, as others have (Belin, 2005), that employing photo-elicitation, in particular, meant it cus of discussions. Elicitation drawing on the visual data gave participants an opportunity to everyday life and the factors that they believed shaped them over the life course (Czarniawska, 2004;Wills et al, 2008;Meah and Watson, 2011;Wills et al, 2011). Informal interviews gave both the participating households, and practices developed and to reveal some of the embedded factors that shaped these experiences.…”
Section: What Is Gained By Using Visual and Non-visual Qualitative Mementioning
confidence: 99%
“…Informal interviews gave both the participating households, and practices developed and to reveal some of the embedded factors that shaped these experiences. Talking with participants helped identify key moments when practices, or a interpretation of practices, might have undergone a shift or rupture at transition points during the life course (Polkinghorne, 1995;Meah and Watson, 2011), such as following bereavement or during pregnancy. Furthermore, analysing video data and then interviewing participants in each household allowed us to more fully investigate the performative aspects associated with a practice (Goffman, 1959), i.e.…”
Section: What Is Gained By Using Visual and Non-visual Qualitative Mementioning
confidence: 99%
See 1 more Smart Citation